The Family-Check-Up® Autism Implementation Research (FAIR) Study: protocol for a study evaluating the effectiveness and implementation of a family-centered intervention within a Canadian autism service setting - Bennett, Teresa; Drmic, Irene; Gross, Julie; Jambon, Marc; Kimber, Melissa; Zaidman-Zait, Anat; Andrews, K.; Frei, Julia; Duku, E.; Georgiades, Stelios; Gonzalez, Andrea; Janus, Magdalena; et al. (Frontiers in Public Health, 2024)
Introduction: Prevalence rates of emotional and behavior problems (EBP) in autistic children and youth are high (40-70%), and often cause severe and chronic impairment. Furthermore, autistic children are also more likely to experience family “social-ecological” adversity compared to neurotypically developing peers, including social isolation, child maltreatment, caregiver mental illness and socioeconomic risk. These family stressors increase the risk of co-occurring EBP among autistic children and can often impede access to evidence-based care, thus amplifying long-term health inequities for autistic children and their caregivers. In the current autism services landscape, there are few scalable, evidence-based programs that adequately address these needs. The Family Check-Up (FCU®) is a brief, strength-based, and tailored family-centered intervention that supports positive parenting and explicitly assesses the social determinants of child and family mental health within an ecological framework. Studies have demonstrated long-term positive child and caregiver outcomes in other populations, but the FCU has not been evaluated in families of autistic children and youth. Therefore, we aimed to evaluate FCU implementation within an established, publicly funded Autism Program in Ontario, Canada, with delivery by autism therapists, to demonstrate sustainable effectiveness within real-world settings. Methods: In this study, we outline the protocol for a hybrid implementation-effectiveness approach with two key components: 1) A parallel-arm randomized controlled trial of N=80 autistic children/youth (ages 6-17 years) and high levels of EBP and their caregivers. Primary and secondary outcomes include child EBP, and caregiver well-being and parenting. 2) A mixed methods implementation study, to describe facilitators and barriers to implementation of the FCU within an autism service setting. Discussion: Scalable, ecologically focused family-centered interventions offer promise as key components of a public health framework aimed at reducing mental health inequities among autistic children, youth and their caregivers. Results of this study will inform further program refinement and scale-up.